2022
DOI: 10.3390/ijerph19138030
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Temporary Workers Engage in More Counterproductive Work Behaviors with Permanent Employees in Chinese State-Own Enterprise: A Social Identity Perspective

Abstract: Why do temporary workers sharing the same working conditions as permanent employees still frequently engage in deviant behaviors that negatively affect the organization’s interests? Drawing on the theory of social identity, this articlr discusses the relationships among employment status, organizational identification, and counterproductive work behavior. Time-lagged data were collected from sample of 210 dyads of employees and corresponding supervisors from a large Chinese state-owned service company, to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 72 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Following social identity theory, temporary employees usually perceive high job insecurity, which concerns the perception of an involuntary and undesired change in the continuity of the work situation (Balz, 2017;Liu X. et al, 2022). Previous studies have shown that organizational commitment is an important factor affecting turnover intention.…”
Section: Organizational Commitment and Turnover Intentionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following social identity theory, temporary employees usually perceive high job insecurity, which concerns the perception of an involuntary and undesired change in the continuity of the work situation (Balz, 2017;Liu X. et al, 2022). Previous studies have shown that organizational commitment is an important factor affecting turnover intention.…”
Section: Organizational Commitment and Turnover Intentionmentioning
confidence: 99%
“…Under the general policy of "no increase but a decrease" in the number of financially-supported staff, the existing stable staffing management can hardly meet the needs of the increased responsibilities. Nonrenewable fixed-term and temporary agency employment contracts began to gradually replace the traditional model of long-term employment, and the proportion of temporary employees in China has continuously increased in recent years (Liu, 2015;Duan et al, 2021;Liu X. et al, 2022). The temporary supernumerary staff has become an important way and channel to make up for the shortage of human resources in government agencies and institutions at all levels (Conway et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations